2017
DOI: 10.1038/srep40652
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-target regression framework for time-series prediction of drug efficacy

Abstract: Excavating from small samples is a challenging pharmacokinetic problem, where statistical methods can be applied. Pharmacokinetic data is special due to the small samples of high dimensionality, which makes it difficult to adopt conventional methods to predict the efficacy of traditional Chinese medicine (TCM) prescription. The main purpose of our study is to obtain some knowledge of the correlation in TCM prescription. Here, a novel method named Multi-target Regression Framework to deal with the problem of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
(38 reference statements)
0
17
1
Order By: Relevance
“…Our results are not in agreement with those of Li et al (2017), who used the multi-trait regressor stacking method for time series prediction of drug efficacy and found that this method was considerably superior with regard to univariate analysis in most datasets they evaluated. The results of the present study are in agreement with those of Melki et al (2017), who evaluated the multi-trait regressor stacking method under the support vector regression framework and found the trick of expanding the predictors in the second stage with the predictions of the target traits in the first stage in order to improve prediction accuracy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are not in agreement with those of Li et al (2017), who used the multi-trait regressor stacking method for time series prediction of drug efficacy and found that this method was considerably superior with regard to univariate analysis in most datasets they evaluated. The results of the present study are in agreement with those of Melki et al (2017), who evaluated the multi-trait regressor stacking method under the support vector regression framework and found the trick of expanding the predictors in the second stage with the predictions of the target traits in the first stage in order to improve prediction accuracy.…”
Section: Discussioncontrasting
confidence: 99%
“…Real-valued Vector River Quality Prediction [22] Ecology Natural Gas Demand Forecasting [23] Energy Meteorology Drug Efficacy Prediction [24] Medicine…”
Section: Independentmentioning
confidence: 99%
“…Multi-target Regression Independent Real-valued Vector River Quality Prediction [22] Ecology Natural Gas Demand Forecasting [23] Energy Meteorology Drug Efficacy Prediction [24] Medicine Label Distribution Learning Distribution Head Pose Estimation [25] Computer Vision Facial Age Estimation [26] Computer Vision Text Mining [27] Data Mining…”
Section: Subfieldmentioning
confidence: 99%
“…MIVs of the 30 common peaks from the 31 different samples were acquired as described in Section 2.8 and the 30 peaks were then ranked by their absolute MIVs, as shown in Table 4. A higher absolute MIV means that the corresponding component contributes more to the inhibition effect of the Fuzi-Gancao extract on HeLa cells, and therefore, the top 8 components (peaks 17,25,22,13,23,28,5,7) are temporarily deemed to possess good antitumor activity. The top 8 components are liquiritin, 14-benzoyldeoxyaconine, benzoylhypaconine, 14-acetyltalatizamine, formononetin, 24-hydroxy glycyrrhetinic acid, senbusine A/B and aconine.…”
Section: Antitumor Component Recognition By MIVmentioning
confidence: 99%
“…Some achievements have been made by this strategy, demonstrating its effectiveness. [3][4][5] To date, various algorithms have been applied to CAR model construction. However, since HMs contain a wide variety of compounds and complicated mutual interactions exist among these components, the commonly used linear models like multiple linear regression analysis (MLR) usually do not t the practical situation very well.…”
Section: Introductionmentioning
confidence: 99%